Is the investment decision affected by the independence and competence of the audit committee? A comparative study between Bahrain and Indonesia. Issue 1 (18th September 2020) - Al-Hadrami, Abdullah Hamza; Rafiki, Ahmad; Sarea, Adel; Nasution, Muhammad Dharma Tuah Putra
Abstract : Purpose: This study aims to investigate the impact of the audit committee's (AC's) independence and competence in the company's investment decision-making in Bahraini- and Indonesian-listed firms, then to compare the two results Design/methodology/approach: A quantitative method is used and cross-sectional data are collected through a self-administered questionnaire survey. A stratified random sample technique is adopted with a total of 409 respondents from 39 listed companies in Bahrain and 303 respondents from 27 companies listed on the Indonesia Stock Exchange (IDX). A descriptive analysis is used to identify the characteristics of the respondents, while a correlation analysis, linear regression and t-test analyses are used to test the model, explain the relationships among variables and compare the two studies (Bahrain vs Indonesia). Findings: It is found that the AC independence and AC competence have a positive and significant influence on investment decision-making for both the Bahrain and the Indonesia studies Practical implications: The current study's results have implications for the process of appointing and nominating the AC members, since this would affect an investor's investment decision. Investors' perception of the independence and competence of ACs will make a difference in their investment decisions. Originality/value: AC independence and competence are importantly crucial for the decision-makers in improving the quality of financial reporting, internal control, and audit. This may lead to an increase in investors' trust in financial reports and their ability to make favorable investment decisions.